Spatio-temporal Modelling of Arterial Road Travel Time Variability - Liu, Yuchen (Curtin University, 2022)
This research systematically investigated and modelled arterial road travel time distributions (TTDs) at various spatial and temporal scales using the travel times derived from a low-cost Bluetooth intelligent transportation system. The characteristics of individual Bluetooth travel times and the evolution pattern of link TTDs in peak periods have been identified. Moreover, two models were developed for estimating path TTDs from individual link TTDs via modelling the dependence in multimodal travel time data.